2019
DOI: 10.1212/wnl.0000000000007089
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of STX1B -related epileptic disorders

Abstract: Objective The aim of this study was to expand the spectrum of epilepsy syndromes related to STX1B , encoding the presynaptic protein syntaxin-1B, and establish genotype-phenotype correlations by identifying further disease-related variants. Methods We used next-generation sequencing in the framework of research projects and diagnostic testing. Clinical data and EEGs were reviewed, including already published cases. To estimate the pathogenicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 41 publications
4
55
0
2
Order By: Relevance
“…We have described the first case of Koolen‐de Vries syndrome caused by a KANSL1 missense mutation (Case 1); all prior cases of Koolen‐de Vries have been caused by either heterozygous deletions or truncation variants . We have also corroborated some of the most recent findings about the multiple phenotypic presentation of STX1B‐related epilepsies . Case 8 is a 44‐year‐old woman with mild ID and cerebellar ataxia who has had focal impaired awareness seizures and temporal epileptiform abnormalities on electroencephalogram (EEG).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…We have described the first case of Koolen‐de Vries syndrome caused by a KANSL1 missense mutation (Case 1); all prior cases of Koolen‐de Vries have been caused by either heterozygous deletions or truncation variants . We have also corroborated some of the most recent findings about the multiple phenotypic presentation of STX1B‐related epilepsies . Case 8 is a 44‐year‐old woman with mild ID and cerebellar ataxia who has had focal impaired awareness seizures and temporal epileptiform abnormalities on electroencephalogram (EEG).…”
Section: Discussionsupporting
confidence: 66%
“…Typically, epilepsy syndromes related to STX1B are either genetic epilepsy with febrile seizures plus or developmental and epileptic encephalopathy. Whereas cerebellar ataxia (present in our patient) has been commonly reported, only two families harboring missense variants have had clinical and EEG findings suggesting temporal lobe onset …”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We also found a network comprising proteins involved in synaptic vesicle release and the guanine nucleotide binding protein GNAO1 ( Figure 7 ), a highly abundant protein in the brain, mutations in which cause severe epilepsy (Nakamura et al, 2013) or movement disorders (Kulkarni et al, 2016) . The mechanistic basis of GNAO1 epilepsy is unknown, but our network suggests that it is caused by disruption of chemical signaling, an inference made stronger by the fact that the other interaction partners, the t-SNAREs syntaxin 1A and B, and Ras-related protein 3A are also implicated in epilepsy (Baghel et al, 2016;Feliciano et al, 2013;Wolking et al, 2019) . Pourhaghighi et al 2019 also found an association between GNAO1 and SNAREs (their Figures 2 and 3), though, interestingly, not the same SNARE proteins, and they do not flag GNAO1 as a disease-related protein (their Figure 3).…”
Section: Inferred Interactions Suggest Novel Mechanisms Underlying Brmentioning
confidence: 95%